Sosialisasi PHBS di MI 03 Jenggot Kota Pekalongan - Putri Andanawarih; Ana Setyowati (LPPM Akbid Harapan Ibu Pekalongan, 2020)
Education about healthy hygiene behavior in school-age children is a critical period as a child to develop good habits that will be used until adulthood. This activity began with a demonstration on how to wash hands and brush the teeth properly. Evaluation is done by giving pre and post test questionnaire verbally. The results obtained are that there is an increase in knowledge of children about healthy hygiene behavior (PHBS) and the activity of children in community service activities.